Influence of semen storage and cryoprotectant on post-thaw viability and fertility of stallion spermatozoa - Melo, C. M.; Zahn, F. S.; Martin, I.; Orlandi, C.; Dell'aqua Junior, José Antônio [UNESP]; Alvarenga, Marco Antonio [UNESP]; Papa, Frederico Ozanam [UNESP] (Elsevier B.V., 2007)
The aim of the current study was to verify that stallion, spermatoza could be cooled for 24 hours and then frozen. In experiment I, one ejaculate from each of 13 stallions was used. Semen was collected and split into two parts; one part immediately frozen using standard cryo-preservation techniques and the other diluted, stored in an Equitainer for 24 hours, and then frozen. In experiment II, one ejaculate from each of 12 stallions was collected, diluted with Botu-Semen, and split into two parts: one cooled in an Equitainer and the other in Max-Semen Express without prior centrifugation. After 24 hours of cooling, the samples were centrifuged to remove seminal plasma and concentrate the sperm, and resuspended in Botu-Crio (R) extender containing on e of three cryoprotectant treatments (1% glycerol + 4% dimethylformamide, 1% glycerol + 4% dimethylacetamide and 1% glycerol + 4% methylformamide), maintained at 5 degrees C for 20 minutes, then frozen in nitrogen vapour. No difference was observed between the two cooling systems. The association of 1% glycerol and 4% methylformamide provided the best post-thaw progressive motility. For experiment III, two stallions were used for a fertility trial. Forty three inseminations were performed using 22 mares. No differences were seen in semen parameters and pregnancy rates when comparing the two freezing protocols (conventional and cooled/frozen). Pregnancy rates for conventional and cooled/frozen semen were, respectively, 72.7% and 82.3% (stallion A), and 40.0% and 50.0% (stallion B). We concluded that cooling equine-semen for 24 hours before freezing while maintaining sperm viability and fertility is possible.
Keywords: equine; cooled and frozen semen; cryo-protectant; fertility